Intel microprocessor : Atchitecture, programming, and interfacing - Brey, Barry B (New Delhi : Pearson, 2009)
The Intel Microprocessors: Architecture, Programming and Interfacing is a comprehensive book for undergraduate students of Computer Science Engineering. The book comprises chapters on addressing modes, arithmetic and logic instructions, using assembly language with C/C++, interrupts, and the arithmetic co-processor. In addition, the book consists of detailed illustrations and relevant examples. This book is essential for software engineers preparing for competitive examinations like GATE and IES.
Appendix A-D 785-915p.; Index 916-926p.
Keywords: Interrupts; Memory interface; Addressing modes